Testing the Theory of Good Thinking and Deciding in Organizational Setting: Many Benefits of Leader’s Actively Open-minded Thinking - Erceg, Nikola; Galić, Zvonimir; Buljan Šiber, Anđela (Studia Psychologica, 2023)
The aim of this work was to test the theory of good thinking and deciding in organizational context by examining the relationships between leaders’ actively open-minded thinking (AOT) and different beneficial organizational outcomes. Across two studies in which we surveyed managers and their subordinates, we have shown that leader’s AOT correlated positively with a range of beneficial outcomes at individual, team and organizational levels. Specifically, managers’ AOT was positively correlated with subordinate-rated decision-making quality and intellectual humility of their superiors, as well as with subordinates’ ratings of their teams’ psychological safety and their own job satisfaction and feeling of organizational support. Some of these effects remained even after controlling for the effects of leader’s personality traits. We conclude that AOT is the disposition that predisposes some leaders to patterns of thinking and behavior that are observable and highly valued by their subordinates, resulting in a range of beneficial outcomes for a company, and that it might be worthwhile to investigate how we can teach leaders to think in more an actively open-minded way.